1995
DOI: 10.1002/acp.2350090106
|View full text |Cite
|
Sign up to set email alerts
|

Helping students acquire belief‐inconsistent and belief‐consistent science facts: Comparisons between individual and dyad study using elaborative interrogatin, self‐selected study and repetitious‐reading

Abstract: One hundred and eighty four grade 6 and 7 students processed 32 factual statements in one of two studies reported here. H a l f the statements were consistent with the students' prior knowledge, whereas the remaining facts were inconsistent with it. Students studied the facts alone, or with a partner, by: (1) answering 'why' questions;(2) reading the information for understanding; or (3) selecting their own method of study. Recall (free and cued) and recognition measures (mediate, 30-day, and 60-day) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…Woloshyn and colleagues (1994) investigated EI's durability in several delayed recognition sessions (14-day, 75-day, and 180-day) and found the learning gains to be durable in all sessions. Other studies confirmed these long-term effects (Kahl and Woloshyn 1994;Woloshyn and Stockley 1995). This study extends the research on elaborative interrogation by examining the benefits of these strategy prompts at a 1-week delay when learners engaged with long, course-related texts.…”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…Woloshyn and colleagues (1994) investigated EI's durability in several delayed recognition sessions (14-day, 75-day, and 180-day) and found the learning gains to be durable in all sessions. Other studies confirmed these long-term effects (Kahl and Woloshyn 1994;Woloshyn and Stockley 1995). This study extends the research on elaborative interrogation by examining the benefits of these strategy prompts at a 1-week delay when learners engaged with long, course-related texts.…”
Section: Methodssupporting
confidence: 53%
“…Several studies have measured the durability of the effectiveness of EI; however, those studies have concentrated primarily on recognition measures such as matching tasks (Kahl and Woloshyn 1994;Willoughby et al 1993), selection of true statements Woloshyn and Stockley 1995), and rating confidence of correct answers (Woloshyn and Stockley 1995). Further, texts used in all of the prior EI durability investigations presented to-be-learned sentences with corresponding elaborative interrogation prompts with each sentence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy has been useful and robust in a multitude of settings. The success of EI prompted researchers to test the strategy with various expository materials, including texts about animals (Willoughby, Waller, Wood, & Mac-Kinnon, 1993;Wood, Pressley, & Winne, 1990), gender differences (Pressley, Symons, McDaniel, Snyder, & Turnure, 1988), Canadian provinces (Martin & Pressley, 1991;Symons & Greene, 1993), West German states (Woloshyn, Pressley, & Schneider, 1992), general science facts (Woloshyn, Paivio, & Pressley, 1994;Woloshyn & Stockley, 1995), Canadian universities (Woloshyn, Willoughby, Wood, & Pressley, 1990), and the human circulatory system (O'Reilly, Symons, & MacLatchy-Gaudet, 1998). Researchers found greater retention with EI strategies in young learners , adolescents (Wood, Willoughby, Kaspar, & Idel, 1994), and adults (Pressley et al, 1988), regardless of presentation formats such as isolated facts (Pressley et al, 1988), sequential facts (Willoughby et al, 1993), paragraphs versus isolated facts (Woloshyn, Willoughby, Wood, & Pressley, 1990), and paragraphs (Seiffert, 1993).…”
mentioning
confidence: 99%
“…Compared to regular conventional courses, Hawkins and Daly (1988) found a stronger involvement of learners in cooperative computer-assisted learning environments. Woloshyn and Stockley (1995) pointed to the high potential of dyadic learning settings, bringing students towards a higher achievement level. A meta-analysis based on 122 studies showed cooperative learning settings to be more efficient than individual learning (Lou et al 2001).…”
mentioning
confidence: 97%